Perceptions of tourism destination and implications for environmental education: Findings from a student field study on protected area, Indonesia - Nugroho, Iwan; Negara, Purnawan Dwikora; Hanafie, Rita; Sudiyono, Sudiyono; Nugroho, Muhammad Ilham (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
University students have an essential role in developing ecotourism services and supporting environmental education. The research aims to explore students' perceptions of the object of tourism, group behavior in travel and problems in tourist destinations. Surveys and interviews were conducted on students who conducted a field study in Coban Tengah tourism destination, Indonesia.  Students of Undergraduate (S1) and Master’s (S2) programs were interviewed regarding tourism objects, group interactions, and problems found in the tourism site. Descriptive analysis and chi-square statistics were carried out to meet research objectives. The results revealed that students show a positive and significant perception of the beauty of Coban Tengah waterfall. S1 students indicated the halo effect phenomenon in perceiving tourism objects regarding beauty, educational element, and trekking paths. Grouping in tourist travel provides benefits to protect or keep safety and serves as a place to discuss environmental conservation.  S2 students are less interested in forming groups because they have more experience and independence in travel than S1 student.  Groups build cooperation and empathy, and these can provide innovation for quality provision of tourism services.JEL Classification I28; Q26; Q58